POLYFUNCTIONALITY OF WORD GROUPS IN UZBEK LANGUAGE - Abdullaeva, Fotima (Журнал иностранных языков и лингвистики, 2021)
In this article, we aim to highlight one of the least studied problems in modern Uzbek linguistics - the polyfunctionality of word groups in the Uzbek language, its structure, linguocultural, functional features and semantic expression